Optimization of the Tunable Nanosecond Cascaded Optical Parametric Oscillators Based on Monolithic Tandem Lithium Niobate Superlattices - Tao Chen; Hao Liu; Wei Kong; Rong Shu (IEEE Photonics Journal)
We report the optimization of tunable nanosecond cascaded optical parametric oscillators (COPOs) based on monolithic tandem lithium niobate superlattices. The nonlinear crystal is designed with a uniform grating section for the optical parametric oscillation process and a linearly chirped grating section for the different frequency generation process. By employing couplers with proper reflectivities and crystals with optimized structures, such tunable COPOs can generate idler waves more efficiently than conventional optical parametric oscillators. It is concluded that higher pump pulse energy and tighter pump beam focus can further improve the pump-to-idler conversion efficiency of such tunable COPOs, particularly for those with wider idler wavelength tuning ranges.